Successful application of chemosaturation with percutaneous hepatic perfusion in metastatic uveal melanoma patient progressing after systemic treatment options: a case report - Gunenc, Damla; Ozluk, Ahmet Anil; Yıldırım, Utku Mahir; Ascierto, Paolo A.; Karaca, Burcak (Frontiers in Oncology, 2024)
Uveal melanoma (UM) is a rare subtype of melanoma, accounting for less than 5% of all melanoma cases. Metastatic UM differs notably from cutaneous melanoma, exhibiting variations in etiology, prognosis, driver mutations, metastatic patterns, and poor responses to immune checkpoint inhibitors (ICI). Beyond local treatment options, such as resection, radiation therapy, and enucleation, and systemic treatments, such as ICIs, the approval of tebentafusp, a bispecific gp100 peptide-HLA-directed CD3 T-cell engager, marks a breakthrough in treating HLA-A*02:01 metastatic UM. Despite the advancements in treatment options, the long-term survival rates remain inadequate. We report a patient with metastatic UM who previously received ICI and progressed on tebentafusp treatment but subsequently exhibited a remarkable response to local treatment targeting liver metastasis. Such observations highlight the significance of exploring sequential therapeutic strategies for advanced UM, offering potential avenues to enhance treatment efficacy and patient prognosis.